STUDENTS' LEARNING ANXIETY IN AN EFL CLASSROOM: LEVELS, CAUSES AND ANXIETY REDUCING FACTORS IN ITS RELATION TO GENDER - Wisnu Wardani, - (2018)
Students in an English as a Foreign Language (EFL) classroom often experience foreign language anxiety (FLA). This foreign language anxiety can affect students' attitude in joining an EFL classroom activity. Research shows that FLA tends to debilitate the students. This case study was aimed to find out what students' levels of anxiety, what factors contributing to the students' learning anxiety and what the anticipated anxiety-reducing factor in an EFL classroom, in its relation to gender. This study employed questionnaires, classroom observation, and semi-structured interview in obtaining the data. This study involved 51 eleventh graders of an Islamic senior high school. There were 24 male students and 27 female students. The male classroom was separated from female classroom. The findings revealed some of contributing factors to learning anxiety such as student's negative self-perception, speaking activity, lack of preparation, comprehending ability, language testing, lack of confidence, being called forward, and fear of being laughed at by peers. According to students' perception there were some anticipated anxiety-reducing factors were found in this study. In relation to the role of teacher, there were being friendly and knowing the students. Regarding teaching instruction, there was the use of students' native language to explain the instruction and the use of appropriate pace were believed that they would be able to reduce the anxiety. Teaching activities which included games, playing song, watching movie, and other media were helpful to reduce the anxiety. The peers could help to reduce the anxiety by giving feedback in positive manner, helping each to others, and having the same interest. ;---Siswa pada kelas Bahasa Inggris sering mengalami kecemasan. Kecemasan bahasa asing ini dapat memengaruhi sikap siswa dalam mengikuti kegiatan kelas bahasa Inggris. Penelitian menunjukkan bahwa kecemasan tersebut cenderung melemahkan siswa. Studi kasus ini bertujuan untuk mengetahui apa saja tingkat kecemasan siswa, faktor apa yang berkontribusi terhadap kecemasan siswa dan faktor apa saja yang dapat mengurangi kecemasan siswa pada kelas Bahasa Inggris, dalam kaitannya dengan gender. Penelitian ini menggunakan instrument berupa kuesioner, pengamatan kelas, dan wawancara. Penelitian ini melibatkan 51 siswa kelas XI Madrasah Aliyah. Ada 24 siswa laki-laki dan 27 siswa perempuan. Ruang kelas laki-laki dipisahkan dari ruang kelas perempuan. Penelitian ini mengungkapkan beberapa faktor yang berkontribusi terhadap munculnya kecemasan diantaranya; persepsi negatif terhadap diri sendiri, aktivitas berbicara, kurangnya persiapan, kurangnya kemampuan memahami, test bahasa, kurang percaya diri, dipanggil ke depan, dan takut ditertawakan oleh teman sebaya. Menurut persepsi siswa ada beberapa faktor yang dapat mengurangi kecemasan yang ditemukan dalam penelitian ini. Terkait dengan peran guru, bersikap ramah dan mengenal siswa. Terkait dengan instruksi pengajaran, penggunaan bahasa Indonesia untuk menjelaskan instruksi yang diberikan dan cara penyampaian instruksi yang tepat diyakini akan dapat mengurangi kecemasan. Kegiatan mengajar yang meliputi permainan, bermain lagu, menonton film, dan penggunaan media lainnya sangat membantu untuk mengurangi kecemasan. Rekan sebaya dapat membantu mengurangi kecemasan dengan memberikan umpan balik dengan cara yang positif, saling membantu satu sama lain, dan memiliki minat yang sama.